The Role of the teacher in developing students' character at MI Muhammadiyah 2 Karangrejo Gresik - Yenny Nur Andini; Bahtiar, Afakhrul Masub (Paedagogia: Jurnal Pendidikan, 2023)
The study aims to analyze the influence of teachers on character building in their students. As well as exploring orientation in the process of building the character of students at MI Muhammadiyah 2 karangrejo. The study used qualitative research design, and the findings show that teachers play an important role in character building to be inspirers and facilitators for their learners. This study identifies several character values instilled in students, including religious, discipline, empathy, diligent, honest, independent, conscientious, responsible, creative, fond of reading, curiosity, peace-loving, tolerance, nationalism, social responsibility, environmental care, love for the motherland. , integrity, and nationalism. The formation of these values is also supported by various factors, such as through school culture with refraction activities, through extracurricular activities, through classroom habituation, and teacher habit activities in opening and closing learning. However, there are also inhibiting factors, such as students who are still affected by negative things from the surrounding environment and also from factors that are not constructive in the community.